POLEMIK SEMUA ORANG MENDATANGI NERAKA DALAM PERSPEKTIF IMAM AL-TABARI - Agus Kharir; Umrana (LP2M Universitas PTIQ Jakarta, 2022)
This article describes about hell in various suras in the Qur'an, one of which is Surah Maryam verses 71 and 72. Unlike other verses, this verse states that everyone will come to hell whether he is a disobedient person or a believer. Regarding this verse, there are differences of opinion on the meaning of the word وَارِدُهاَ which means to come to him. Some interpret it with the meaning of entering. While some others interpret it with the meaning of passing. Imam al-Tabari is one of the commentators who provides a fairly detailed interpretation of the verse. The author uses a qualitative method of literature (library research) with the theory of tahlili. The author conducts a search and collects various data related to the variables studied, then analyzes interpretively and descriptively on the data that has been collected. The meaning of the word وَارِدُهاَ in this verse according to al-Tabari is al-Mururu or passing, that is, all believers or unbelievers will pass through hell, namely through sirat that lies above hell. But among them there are those who survived through it and some who fell into hell. Regarding the criteria for those who are saved on the journey through the sirat, Imam al-Tabari stated that they are pious people. As for the criteria for those who are allowed to fall into hell according to al-Tabari, they are those who wrong themselves